A new anomaly observed in 4He supporting the existence of the hypothetical X17 particle. (December 2020) - Krasznahorkay, A. J.; Csatlós, M.; Csige, L.; Gulyás, J.; Koszta, M.; Szihalmi, B.; Timár, J.; Firak, D.S.; Nagy, Á.; Sas, N.J.; Krasznahorkay, A.
Abstract: Recently, we observed an anomalous peak-like excess of internal e + e − pairs at around 140° for the M1 transition depopulating the 18.15 MeV isoscalar 1 + state in 8 Be. The deviation from the theoretical prediction can be described by GEANT simulations assuming the creation and subsequent decay of a new, light boson with a mass of 16.7 MeV/c 2 . In order to reduce the possible systematic errors from the experimenntal data, we re-investigated the 8 Be anomaly with an improved setup and confirmed the anomaly within the statistical uncertainties. We also studied the angular correlation of the electron-positron pairs created in the M0 transition depopulating the 21.01 MeV 0 − state in 4 He, and observed an anomalous excess of e + e − pairs at a significantly smaller angle of 115°. Since the transition energy was higher in this case, the observed anomaly could be described by assuming the creation and subsequent decay of the same light particle in the simulations.